THU0178 Clinical significance of rapid radiographic progression in rheumatoid arthritis. (1st June 2001) - Wong, JB; Wong, CJ; Hazes, JM; Van Riel, PL; Breedveld, FC; Van der Heidje, DM; Feagan, BG
Abstract : Background: New treatments for rheumatoid arthritis have established radiographic stabilisation of joint disease as an achievable therapeutic goal, but the amount of radiologic progression that is clinically significant remains uncertain. OMERACT has defined significant radiographic progression by the smallest detectable difference (SDD) based on random measurement error calculated from between observer variation in pairwise radiographic scoring and interpretation. Objectives: To examine the clinical significance of SDD-defined radiographic progression. Methods: We combined 2 Dutch cohorts of early rheumatoid arthritis patients from Nijmegen and Leiden. Using an SDD of 15 for the modified Sharp score, 279 patients had year 2 or 3 radiographs (mean age 50.5 year, 76.7% women, 71.7% RF+, 60.1% HLA DR4+) and were divided into 2 groups based on their annual radiographic progression rate: rapid (>7.5) vs non-rapid (<7.5) radiographic progressors. Exploratory statistical analyses were performed using the Chi-square and Wilcoxon rank sum tests. Results: In this cohort, 199 of the 279 patients (71%) were ?rapid progressors? after 2 – 3 years of RA. At that time, fast progressors tended to be HLA DR4+ (p = 0.11) but had higher ESR, Ritchie articular index, HAQ and Disease Activity Scores (DAS) (all p < 0.02), and were more likely to be older and RF+ (all p < 0.0001). After 5 – 6 years of RA, fast progressors had higher median modified Sharp scores (102 vs 8, p < 0.0001), HAQ scores (0.50 vs 0.23, p < 0.003), and DAS (2.80 vs 2.02, p = 0.003). After 12 years of RA, fast progressors had higher median HAQ (0.88 vs 0.26, p = 0.013) and DAS (2.88 vs 2.35, p = 0.11). Conclusion: Although SDD-based radiographic progression is defined as a statistically significant worsening beyond random measurement error, such radiologic progression of joint disease appears to identify rheumatoid arthritis patients who are significantly more likely to experience clinically progressive disease. Identifying and targeting the use of new biologic therapies toward this group of radio logically rapidly progressive rheumatoid arthritis patients is likely to yield the most favourable cost-effectiveness ratios because in the absence of these new treatments, these patients are at higher risk of developing progressive disability.